Construction of Three Novel Oxygen-Containing Cagelike Frameworks and Synthesis of their Energetic Derivatives - Li, Huan; Zhou, Qi; Zhao, Jingjing; Hou, Tianjiao; Wang, Guixiang; Zhu, Long; Li, Bing; Zhang, Yu; Luo, Jun (Synlett, 2024)
Organic cagelike frameworks are important and versatile skeletons for developing prospective energetic compounds because of their high intrinsic density, symmetry, stability, and derivability. Herein, we show the construction of three novel cagelike frameworks including dioxaadamantane, dioxaproadamantane, and dioxatwistane from 9-oxabicyclo[3.3.1]nonane-2,6-diene. In addition, their energetic derivatives were also prepared and characterized. Compared with our previous works, the introduction of more oxygen atoms into the framework gives the corresponding energetic derivative a better oxygen balance, significantly higher density, and detonation properties. These results imply that the oxygen-containing framework has the potential to be used for preparing new 3D energetic compounds with superior energy performance.
Keywords: cagelike compounds; oxygen-containing frameworks; energetic compounds; synthesis; performance; oxidative cyclization; oxidation; nitration